1992
DOI: 10.3109/00016489209137444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Diazepam and Thiopental on Voluntary Saccades and Pursuit Eye Movements

Abstract: The effects of diazepam and thiopental on voluntary saccades and pursuit eye movements were tested in 9 volunteers, with an interval of at least 2 weeks between tests. One, 4 and 8 h after intravenous injection of diazepam (0.3 mg/kg) or thiopental (6.0 mg/kg), voluntary saccades and pursuit eye movements were tested and blood samples taken for analysis of drug concentration. As compared to results of tests without drugs, a significant reduction both of saccadic peak velocity and gain of pursuit eye movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Similarly, Padoan et al [11] showed an increase in saccadic latency following the intravenous delivery of 6.0 mg.kg ¹1 of thiopentone. Although the experiments reported here were not double-blinded, as it was not possible to disguise the metallic taste of isoflurane, in the case of the countermanded protocol there appears to be no placebo effect, and this is also likely to be true with respect to simple latency.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Padoan et al [11] showed an increase in saccadic latency following the intravenous delivery of 6.0 mg.kg ¹1 of thiopentone. Although the experiments reported here were not double-blinded, as it was not possible to disguise the metallic taste of isoflurane, in the case of the countermanded protocol there appears to be no placebo effect, and this is also likely to be true with respect to simple latency.…”
Section: Discussionmentioning
confidence: 82%
“…This pattern of results raises the possibility that the reduc tion in slow-target-gain after apomorphine was second ary to sedation. A number of compounds with sedat ing effects have been found to reduce smooth pursuit gain, including barbiturates (Padoan et al 1992), ben zodiazepines (Rothenberg and Selkoe 1981;Bittencourt et al 1983;Padoan et al 1992), alcohol (Baloh et al 1979;Barnes et al 1984;Tedeschi et al 1984;Stapleton et al 1986), nitrous oxide (Magnusson et al 1989), and metha done (Rothenberg et al 1980). However, in an acute study of the effects of chlorpromazine on eye move ments, Holzman et al (1975) found no effect on eye tracking in the presence of a large soporifIc effect.…”
Section: Discussionmentioning
confidence: 97%
“…Smooth-pursuit gain reduction is known to appear in various other conditions, including barbiturate and [28,30] diazepam administration [28], inattention [5] and schizophrenia [24] and is also seen rather unspecifically in other neurological and psychiatric disorders [22]. Control of smooth-pursuit eye movements involves parts of the pontine nuclei, vestibulo-cerebellum, cerebellar vermis, extrastriate visual cortex, frontal eye fields, and parietal lobe [13,22].…”
Section: Smooth-pursuit Eye Movementsmentioning
confidence: 99%
“…Alcohol consumption leads to prolonged oculomotor reaction times in response to visual stimuli, but it has also been suggested to induce disturbances in basic and complex visual and ocular motor functions [2,28]. Measurement of eye movements by the infrared reflection technique is a reliable method for assessing dysfunctions of the visuomotor system [23][24][25].…”
Section: Introductionmentioning
confidence: 99%